Control interno contable - financiero del activo corriente de la Asociación De Mariscadores Autónomos Y Anexos 11 De Enero. - Vera Vera, Blanca Isabel (My University, 2019)
The purpose of this research work is to publicize the shortcomings that exist during the period 2017, in the management of income and expenses within the Association of autonomous shellfish and annexes January 11 causing lack of control in accounting processes causing possible deviations of money. The limited internal control fails to comply with the application of rules and procedures in the accounting and financial aspects, this does not allow knowing exactly the level of liquidity of the institution where you can not have confidence in the information provided thereby ignoring the financial reality of the same. The work focuses on the management of cash, as is the organization about collections and payments if these items are properly supported above all payments, previously there have been reports where an exit is presented two to three times a year, without It should be highlighted that the institution does not have a small cash fund evidenced a serious fault in the accounting processes. The main objective is to evaluate the internal accounting - financial control of current assets to improve the financial information of the organization, applying the logical deductive and observational method, relying on documentary - bibliographic and observational research. During the development of the investigation, audit concepts, auditing standards, control bodies, current assets and other issues that are essential to reason the problem to be discussed are discussed, which will allow a broad vision of where you want to reach with this analysis. Through the application of instruments such as the interview, observation guide, application of financial indicators and a strictly necessary comparison between the operations of the Association with the regulations of the Superintendence of Popular and Solidarity Economy, regulator of the institution, this will allow to know the the reality of the organization, the appreciation that its directors have of it and if they are aware of the provisions issued by the Popular and Solidarity Economy Law, to what extent they are met in the development of operations, in addition to the management of the transactions and the corresponding accounting record according to the single catalog of accounts. The financial indicators provide data to know the behavior of the company, evaluating the financial situation by interpreting them if this is positive or negative, how much is the security that provides through the financial statements. All this leads to the formulation of conclusions which will expose the failures and errors found during the investigation, proposing in the solutions solutions so that the correct internal control that every institution should have is made more viable, emphasizing the use of accounting tools that allow an adequate collection of income, better organization of information, that expenditures are duly supported by the required documentation, these changes will make the organization optimize its accounting processes apply standards, procedures and provisions improving the reliability of information, the veracity in the financial statements and the efficiency of the Association.
El propósito de este trabajo investigativo es dar a conocer las falencias que existen durante el período 2017, en el manejo de los ingresos y egreso dentro de la Asociación de mariscadores autónomos y anexos 11 de enero provocando falta de control en los procesos contables originando posibles desvíos de dinero. El escaso control interno incumple con la aplicación de normas y procedimientos en los aspectos contables y financieros, esto no permite saber con exactitud el nivel de liquidez de la institución en donde no se puede tener confianza de la información proporcionada por ende desconociendo la realidad financiera de la misma. El trabajo se enfoca en el manejo del efectivo, como es la organización acerca de los cobros y pagos si estos rubros están debidamente respaldados sobre todo los pagos, anteriormente han existido informes en donde un egreso es presentado dos hasta tres veces en el año, sin que sea respaldado como tiene que ser, cabe destacar que la institución no cuenta con el fondo de caja chica evidenciado una falta grave en los procesos contables. El objetivo principal es evaluar el control interno contable - financiero del activo corriente para mejorar la información financiera de la organización, aplicando el método lógico deductivo y observacional, apoyándose en la investigación documental – bibliográfica y observacional. Durante el desarrollo de la investigación se exponen conceptos de auditoria, normas de auditoria, organismos de control, activo corriente y otros temas que son indispensables para razonar el problema a tratar lo cual consentirá una amplia visión de hacia donde se desea llegar con este análisis. Mediante la aplicación de instrumentos como la entrevista, guía de observación, aplicación de indicadores financieros y una comparativa estrictamente necesaria entre las operaciones de la Asociación con la normativa de la Superintendencia de Economía Popular y Solidaria, ente regulador de la institución, esto permitirá conocer la realidad de la organización, la apreciación que tienen de la misma sus directivos y si ellos tienen conocimiento de las disposiciones emitidas por la Ley de Economía Popular y Solidaria, a que grado se cumplen con las mismas en el desarrollo de las operaciones, además del manejo correcto de las transacciones y el correspondiente registro contable conforme al catálogo único de cuentas. Los indicadores financieros proveen datos para conocer el comportamiento de la empresa, evaluando la situación financiera mediante la interpretación de los mismos si esta es positiva o negativa, cuánto es la seguridad que brinda a través de los estados financieros. Todo esto conlleva a la formulación de conclusiones donde se expondrán las fallas y errores encontrados durante la investigación proponiendo en las recomendaciones soluciones para que se haga más viable el correcto control interno que toda institución debe tener, haciendo énfasis en el uso de instrumentos contables que permita una captación adecuada de los ingresos, mejor organización de la información, que los egreso estén debidamente respaldados por la documentación requerida, estos cambios harán que la organización optimice sus procesos contables aplique normas, procedimientos y disposiciones mejorando la confiabilidad de la información, la veracidad en los estados financieros y la eficiencia de la Asociación.
Keywords: CONTROL INTERNO; ACTIVO CORRIENTE; ECONOMÍA POPULAR Y SOLIDARIA; DISPONIBLE